Postoperative Imaging of Bioabsorbable Anchors in Rotator Cuff Repair. (March 2014) - Kim, Sae Hoon; Oh, Joo Han; Lee, O-Sung; Lee, Hwa-Ryeong; Hargens, Alan R.
Background: Bioabsorbable anchors may lead to osteolysis and cyst formation. However, the prevalence of these outcomes is not known for rotator cuff repairs. Purpose: To evaluate cyst formation after placement of bioabsorbable anchors for rotator cuff repairs and to verify whether bioabsorbable anchors degraded as intended and preserved bone stock for possible revision compared with metal anchors. The null hypothesis was that the rate and severity of cyst formation around the anchor are negligible. Study Design: Case series; Level of evidence, 4. Methods: Between April 2008 and November 2011, a total of 209 patients (85 men, 124 women) underwent rotator cuff repair with bioabsorbable suture anchors (113 with polylactic acid enantiomers [PLLA] and 96 with poly-D, L-lactide from L-lactide and D-lactide [PLDLA]); the patients underwent magnetic resonance imaging (MRI) evaluation more than 10 months after surgery. The fluid signal around the anchor on T2-weighted MRI scans was graded as follows: grade 0, no fluid around anchor; grade 1, minimal fluid around anchor; grade 2, local fluid around anchor; grade 3, fluid collection around entire length of anchor with cyst diameter less than twice the anchor diameter; and grade 4, cyst diameter larger than grade 3. The integrity of repairs was also evaluated. Results: Cysts were observed in 97 instances (46.4%). There were 41 grade 1 cases (19.6%), 16 grade 2 (7.7%), 22 grade 3 (10.5%), and 18 grade 4 (8.6%). Healing of repaired tendon was observed in 131 patients (62.7%). There was no statistical difference in healing rate between patients with and without cyst formation (66.1% vs 58.8%; P = .276). Altered anchor shape and absorption were not observed in most of the patients. However, in 12 patients (6 with PLLA and 6 with PLDLA anchors), T2-weighted scans showed that the signal intensity of anchors had changed since surgery, which could indicate that absorption had taken place; nonetheless, even in these 12 patients, anchors were clearly visible on T1-weighted scans. Conclusion: Osteolysis and cyst formation are common complications following the use of bioabsorbable anchors in rotator cuff repairs. Considering that adequate absorption of anchors and preservation of bone stock are the reasons for using bioabsorbable anchors, use of these anchors should be reconsidered because of possible interference with revision surgery.